Implementasi Konsep Tri Hita Karana Dalam Konservasi Taman Nasional Alas Purwo Berbasis Kearifan Lokal (Jurnal Hutan dan Masyarakat, 2023)
This study describes the lives of the people around Alas Purwo National Park buffer village that has local wisdom. Man with his intelligence can create an order in relation to God, fellow human beings, as well as relationships with nature. The most basic and urgent value in reconstructing local wisdom is the correlation of Tri Hita Karana implementation with conservation rules. The type of research used is descriptive qualitative with case study design. The results showed that the community around Alas Purwo National Park area has local wisdom in the form of a number of traditions, rules or restrictions that are still valid for generations which are then maintained and obeyed until now in managing forests to remain sustainable.Keywords: Kerinci Tri Hita Karana, Conservation, Alas Purwo National Park, Local Wisdom